Preserflo MicroShunt Implantation: A Narrative Review of Its Standalone Benefits vs. Combined Use with Phacoemulsification in Managing Open-Angle Glaucoma - Małgorzata Chilmonczyk; Kinga Gołaszewska; Emil Saeed; Joanna Konopińska (Ophthalmology and Therapy)
Abstract Glaucoma and cataract often coexist. Patients with both conditions who qualify for surgical treatment may undergo either a combined surgical procedure or sequential treatments such as cataract surgery followed by an antiglaucoma procedure. A combined procedure with phacoemulsification is related to an increased risk of fibrosis of the filtering bleb; however, it is a rational approach for patients with high intraocular pressure and clinically significant lens opacification. Trabeculectomy has been a traditional filtration procedure for decades, effectively lowering intraocular pressure. It is highly effective; however, it may cause sight-threatening complications. The Preserflo MicroShunt, introduced less than a decade ago in the field of glaucoma surgery, has shown similar hypotensive efficacy to trabeculectomy, and is a less invasive procedure with a better safety profile. Despite their shared mechanism of action to reduce intraocular pressure, the two procedures differ in the extent of scleral incision and filtration bleb morphology, which may influence the extent of the post-surgery inflammation process. This review evaluated and compared reports on the efficacy and safety of Preserflo MicroShunt implantation as a standalone procedure versus combined with cataract removal in surgical treatment for patients with open-angle glaucoma and concomitant cataract.